2017
DOI: 10.1097/aco.0000000000000450
|View full text |Cite
|
Sign up to set email alerts
|

The use of ultrasound in obstetric anesthesia

Abstract: Anesthesiologists have clearly embraced this facile versatile tool for bedside diagnostics and procedures. One limitation to widespread adoption is availability of suitable ultrasound skills and technology. Many of these ultrasound techniques have not yet established clear patient benefit, yet the sheer breadth of ultrasound techniques reported in the past few years demonstrate that our colleagues are becoming more proficient. It is important to follow the development of this emerging field to be aware of limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…Hui et al [11] used ultrasonography to image the sublingual space in a non-pregnant population. Sublingual USG has been shown to be well tolerated, and it has been reported that this technique may be relevant in pregnant women [12].…”
Section: Discussionmentioning
confidence: 99%
“…Hui et al [11] used ultrasonography to image the sublingual space in a non-pregnant population. Sublingual USG has been shown to be well tolerated, and it has been reported that this technique may be relevant in pregnant women [12].…”
Section: Discussionmentioning
confidence: 99%
“…В дополнение к эхокардиографии в настоящее время все чаще используются и другие ультразвуковые методы оценки состояния акушерских пациенток для определения тактики дальнейшей терапии. Так, один из современных источников литературы [26] демонстрирует описание возрастающей роли ультразвукового исследования для акушерской анестезиологии, в том числе при: а) диагностике трудного дыхательного пути, учитывая сложности интубации и вентиляции, характерные для беременности. При этом своевременное выявление пациенток с особенностями дыхательных путей позволяет провести подготовку согласно соответствующему протоколу или выбрать, если возможно, альтернативный метод анестезии; б) определении объема и наличия содержимого желудка (для выявления пациенток с высоким риском регургитации и аспирации); в) диагностике внутричерепной гипертензиипо увеличению диаметра оболочки зрительного нерва, характерного для ПЭ; г) обеспечении сосудистого доступа, что на фоне гипергидратации тканей при беременности -сложная задача; д) выполнении нейроаксиальных блокад и блокады поперечного пространства живота; е) определении объема инфузионной терапии, чрезвычайно важном этапе интенсивной терапии тяжелых гипертензивных нарушений [27,28].…”
Section: значение эхокардиографии и данных ультразвукового исследованunclassified
“…Nowadays, as higher quality ultrasound machines have become more available and inexpensive, so their popularity has risen further as a technique for diagnosis and procedures at bedside. 6 The majority of peripartum women that anesthesiologists involved with, are at low risk for developing complications, but still the possibility for serious scenarios that threaten the health and life of both the mother and her fetus can occur. These may happen in a low-risk unit, and can rapidly develop, making it difficult to secure a specialist for diagnostic help.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It is attractive to imagine being able to visualize the needle journey through the anatomical structures till it ends in the epidural space in real time. 6…”
Section: Neuraxial Blocksmentioning
confidence: 99%